Friction Compensated Force Control of Electro-Hydraulic System Using Fuzzy Controller - Weerapong Chanbua; Unnat Pinsopon (My University, 2022)
Steady state and dynamic LuGre friction models of an electro-hydraulic system were constructed.Indirect electro-hydraulic cylinder force control under friction compensated PID and fuzzy controllers were tested and compared.Feedback force signal was indirectly measured and calculated from pressures to emulate the applications that direct force measurement is impossible.Estimated friction was compensated to desired force command of the PID controller.The proposed fuzzy controller contained two modules.The first, as a friction compensator, calculated modified error according to estimated friction and feedback force error.The second module calculated control action based on PD control scheme.Friction compensated PID and fuzzy controllers could reduce tracking errors at the maximum force commands by 80% and 90%, respectively, compared to the PID controller without compensation.The steady state friction compensation yielded better tracking performances compared to the dynamic friction.Tracking performance of the fuzzy controller was always better than the PID controller.
Keywords: Hydraulic and Pneumatic Systems